Prevalence and associated factors of probable depression amongst pregnant and parenting young females: a comparison of adolescents and young adults in rural South Africa - Seakamela, K. P.; Mashaba, R. G.; Ntimana, C. B.; Mbombi, M. O.; Tlouyamma, J.; Mphekgwana, P.; Nemuramba, R.; Mothapo, K.; Muthelo, L.; Mabila, L. N.; Dhau, I.; Maimela, E. (Frontiers in Child and Adolescent Psychiatry, 2023)
Background: Pregnant teenagers have been reported to have an increased likelihood to experienceof experiencing depression than their non-pregnant peers. There is little research on the risk factors for depression in rural Black adolescents and young adults, especially after the Covid-19 pandemic. Therefore, the current study aimed to identify the prevalence of depressionprobable depression and associated factors amongst pregnant and parenting young females.The study was a cross–sectional in design, consisting of 362 pregnant and parenting adolescents and young adults aged 14 to 22. The study used the Edinburgh Postnatal Depression Scale (EPDS) to measure depressionprobable depression. Data were analysed analyzed using Statistical Package for Social Sciences SPSS, version 27.0.The study found that the overall prevalence of depressionprobable depression was 42.8%. The study also found a relationship between alcohol consumption, lack of financial support, unplanned pregnancy, and depressionprobable depression in pregnant and parenting adolescents. The prevalence of unplanned pregnancy in the present study was 81.8%.